An Overview of the Resistance of Insulin - Edan, Luma Mahmood; Ali, Ruaa H.; JAWAD, ASMAA A.; Kadhom, Tay Hatem; Bedair, Nada H.; Jafar, Saba R.; Hameed, Mohammed Ayad; Muhi, Shahrazad H. (Al-Salam Journal for Medical Science, 2024)
Obesity and diabetes are becoming widespread in industrialized nations, reaching epidemic proportions. As a result, there is an increasing awareness of the importance of insulin resistance and its related consequences. An in-depth understanding of insulin's role in several physiological processes, its influence on its own synthesis and secretion, and its consequences at both the molecular and systemic levels is highly important for the understanding of several chronic diseases prevalent in Western populations today. This article provides a thorough analysis of insulin, including its historical context, structural makeup, synthesis methods, secretion processes, many functions, and interrelationships. Afterwards. This study also includes evaluations of insulin resistance from both clinical and functional perspectives.